Brands in the arts and culture sector. Issue 1 (29th April 2014) - Baumgarth, Carsten; O'Reilly, Daragh
Abstract : Purpose: – The purposes of this editorial are first, to review the background to, and development of, the Special Issue call for papers issued in March 2013 on the topic of "Brands in the Arts and Culture Sector", second, to introduce the eight papers in the double issue (seven in the Special Issue plus one paper (by Caldwell)) which was submitted to the journal in the normal course and whose topic fits well with the arts and cultural branding topic, and third, to set out a framework designed to facilitate the analysis of individual arts and cultural brands, as well as the directions for future research in the area. Design/methodology/approach: – The papers in this Special Issue use a variety of approaches-some qualitative (e.g. ethnography, expert interviews), others quantitative (e.g. laboratory experiment, surveys); others deal with conceptual issues for individual artists and for the arts market. Findings: – Findings and insights relate to topics such as: how the "in-between spaces" (e.g. art studios) can be key building blocks of a strong artist's brand; the importance of western ideas for the Chinese art market; how pro-activeness, innovation, and risk-taking are the three key drivers for the decision to integrate blockbusters as a sub-brand in museum brand architecture; the importance of experiential design for low-involvement museum visitors; the utility of the notion of brand attachment in explaining volunteering; the potential of visual arts branding for general branding theory; the concept of millennial cultural consumers and how to reach them; and celebrity casting in London's West End theatres. Research limitations/implications: – The authors believe that all of the papers have implications for future thinking, research, scholarship, paedagogy, and practice in the area of arts and cultural branding. Originality/value: – As far as the editors are aware, this is the first ever journal Special Issue on arts and cultural branding. More specifically, the authors have taken the opportunity to present in this editorial essay the "C-Framework" of arts and cultural brands, which offers a new way of thinking about arts and cultural brands − one which can accommodate classical or so-called "mainstream" branding ideas as well as insights from cultural, media, and consumer studies, and other disciplines. This framework can be applied to individual arts and cultural brands as well as to the entire field.